Royal inscriptions on clay cones from Ashur now in Istanbul - Donbaz, Veysel; Grayson, Albert Kirk (University of Toronto Press, 1984)
""K: Unidentified Fragments: Texts 249-308""""Indexes""; ""A. Index of Excavation Numbers""; ""B. Index of Museum Numbers""; ""C. Index of Previous Publications""; ""A""; ""D""; ""G""; ""L""; ""M""; ""R""; ""S""; ""W""; ""D. Names of Rulers Attested""; ""Plates""